Strategi DPR RI Dalam Meningkatkan Transparansi di Media Sosial: Studi Kasus Youtube TV Parlemen - Nurholizah, Titi; Aji, Muhammad Prakoso (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study analyzes the transparency strategy of the Indonesian House of Representatives (DPR RI) through its YouTube channel, TV Parlemen, as part of the legislature’s digital communication. The research is motivated by low public trust in the DPR and the growing demand for open, accessible political information in the digital era. It aims to examine how transparency is implemented via TV Parlemen and to assess the effectiveness of this channel in promoting public access to information. Using a descriptive qualitative method, data were collected through in-depth interviews with officials from the Parliamentary News Bureau, the Head of TVR Parlemen, and political observers, complemented by observation of TV Parlemen content and analysis of supporting documents. The findings show that transparency through YouTube remains largely procedural. Although information is opened via live streaming of plenary and commission meetings, the content is dominated by long formats, technical language, and limited contextual explanation, making it difficult for the general public to understand. Mechanisms of agenda setting and quality control also keep openness within institutional boundaries by filtering certain issues, while the interactive features of social media are underutilized. TV Parlemen tends to operate as a one-way documentation channel, reflected in a very low engagement rate of around 0.01%. The study concludes that the channel functions more as an archive than as a medium of substantive transparency, and recommends more concise, contextual, and interactive content packaging to strengthen public understanding and participation.